Whose Odyssey Is It? Family-Centered Care in the Genomic Era - Brosco, Jeffrey P. (The Hastings Center report, 2018)
Despite a century of progress in medical knowledge, many diagnostic odysseys end in disappointment, especially when the child has a developmental disorder. In cases of autism and intellectual disability, relatively few children receive a specific diagnosis, and virtually none of those diagnoses lead to a specific medical treatment. Whole-genome or -exome sequencing offers a quantum leap in the diagnostic odyssey, in that we will always learn something from sequencing—sometimes much more than families bargained for, as discussed elsewhere in this special report. The trick is whether the knowledge gained will help the child and family. A family-centered approach gives families permission to choose but does not lay all of the responsibility on them. The goal is to pursue the degree of medical diagnostic evaluation that matches the family's values.